Fission yeast Cactin restricts telomere transcription and elongation by controlling Rap1 levels. (14th November 2014) - Lorenzi, Luca E; Bah, Amadou; Wischnewski, Harry; Shchepachev, Vadim; Soneson, Charlotte; Santagostino, Marco; Azzalin, Claus M
Abstract The telomeric transcriptome comprises multiple long non‐coding RNAs generated by transcription of linear chromosome ends. In a screening performed in Schizosaccharomyces pombe, we identified factors modulating the cellular levels of the telomeric transcriptome. Among these factors, Cay1 is the fission yeast member of the conserved family of Cactins, uncharacterized proteins crucial for cell growth and survival. In cay1∆ mutants, the cellular levels of the telomeric factor Rap1 are drastically diminished due to defects in rap1+ pre‐mRNA splicing and Rap1 protein stability. cay1∆ cells accumulate histone H3 acetylated at lysine 9 at telomeres, which become transcriptionally desilenced, are over‐elongated by telomerase and cause chromosomal aberrations in the cold. Overexpressing Rap1 in cay1+ deleted cells significantly reverts all telomeric defects. Additionally, cay1∆ mutants accumulate unprocessed Tf2 retrotransposon RNA through Rap1‐independent mechanisms. Thus, Cay1 plays crucial roles in cells by ultimately harmonizing expression of transcripts originating from seemingly unrelated genomic loci.